The function of VAMP2 in mediating membrane fusion: An overview - Yan, Chong; Jiang, Jie; Yang, Yuan; Geng, Xiaoqi; Dong, Wei (Frontiers in Molecular Neuroscience, 2022)
Vesicle-associated membrane protein 2 (VAMP2) encodes the cystic SNARE protein VAMP2, which is also known as Synaptobrevin 2. It has been demonstrated that VAMP2 plays a prominent role in initiating the assembly of Soluble N-ethyl maleimide sensitive factor attachment receptor (SNARE) complex. Therein, VAMP2 combined with Syntaxin-1A (Syx-1A) and synaptosome associated protein of 25kDa (SNAP-25) produce a force to induce the formation of fusion pores, thereby mediating the fusion of synaptic vesicles and neurotransmitters release. Before the formation of SNARE complex, the structure of VAMP2 is unclear, considered to be largely unstructured. Following the interaction with other cooperating SNARE partners, VAMP2 can form four structured domains. In this review, we highlight recent progresses of the roles of VAMP2 domains and the interaction between VAMP2 and various fusion-related proteins in presynaptic cytoplasm during the fusion. Our summary will contribute to better understand of the roles of VAMP2 protein in membrane fusion and in human neural development diseases.